2003
DOI: 10.1007/s00248-001-1068-7
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Rise in Mercury-Resistant Bacteria in Coastal Environs

Abstract: A sharp rise in mercury-resistant bacteria (MRB) capable of tolerating very high concentration of Hg was observed over the last 3-4 years in the coastal environs of India. While none or negligible colony-forming units (CFU) of bacteria were counted on seawater nutrient agar with 0.5 ppm ( 2.5 microM) Hg (II) as HgCl2 until 1997, from 13 to over 75% of the CFU grew on 20 times higher, 50 microM, Hg concentrations from almost every recently examined marine sample. Although exceptionally high counts of MRB (96% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 39 publications
2
17
0
1
Order By: Relevance
“…In addition, the collection bacteria from IFD contained the lowest percentage of Cu-and Cd-sensitive bacteria. Elevated levels of metal-tolerant Bacteria in soils and sediments after exposure to heavy metals have been described previously (Diaz-Ravina and Baath 1996;Ramaiah and De 2003;Rasmussen and Soerensen 1998), but not in combination with detailed metal analyses indicating such localized and short-term metal exposure.…”
Section: Effects Of Sediment Homogenization and Redepositionmentioning
confidence: 63%
“…In addition, the collection bacteria from IFD contained the lowest percentage of Cu-and Cd-sensitive bacteria. Elevated levels of metal-tolerant Bacteria in soils and sediments after exposure to heavy metals have been described previously (Diaz-Ravina and Baath 1996;Ramaiah and De 2003;Rasmussen and Soerensen 1998), but not in combination with detailed metal analyses indicating such localized and short-term metal exposure.…”
Section: Effects Of Sediment Homogenization and Redepositionmentioning
confidence: 63%
“…In order to quantify and understand their relationship with relevant environmental factors, several investigators have examined distribution of these groups of bacteria and certain viruses in coastal waters (Colwell et al 1977;Marchand 1986;Patti et al 1987;Piccolomini et al 1987;Ramaiah and Chandramohan 1993;Ruiz et al 2000;Ramaiah and De 2003). Mortality and survival rates of fecal contamination indicator Escherichia coli in the marine regimes have also been studied (Thom et al 1992;Darakas 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Till date, there is no data available for such high tolerance of mercury in aerobic bacteria. Frischmuth et al (1993) and Ramaiah and De (2003) reported several bacterial strains with tolerance up to 100 lg/g for mercuric chloride in solid and liquid medium.…”
Section: Resultsmentioning
confidence: 99%